URGENSI SIRAH NABAWIYAH BAGI PEMAHAMAN HADIS NABAWI - Musyafiq, Ahmad (At-Taqaddum, 2013)
One reason for the importance of understanding the hadits is talking about the existence of the problems associated with exploring hadits aspect such as wurud aspect, dalalah aspect, and comprehensive aspect. This paper will elaborate on how the urgency of Sirah Nabawiyah for understanding the hadits through three aspects.Through this study of literature was found few things. First, the urgency of Sirah Nabawiyah in uNabawiyah in understanding Prophetic Hadits can be seen through three problems of understanding hadits such as wurud problem, dalalah problem and comprehensive problem. In the wurud problem of Prophetic hadits, the urgency of Sirah Nabawiyah shown as one of the benchmark of matan criticism in its position.In the dalalah problem of prophetic hadits, the urgency of Sirah Nabawiyah shown in its position as a provider of data of contextual hadits which is more extensive than Asbab al-Wurud al-Khassah and also clearer and more valid than Asbab al-Wurud al-?Amma. Thus, Sirah Nabawiyah is a solution to the drawbacks faced by Asbab al-Wurud al-Khassah and Asbab al-Wurud al-?Ammah. In the comprehensive problem of prophetic hadits, the urgency of Sirah Nabawiyah shown in its position as a partner for the prophetic hadits in providing complete data about the Prophet Muhammad SAW. This is reflected in three ways such as Sirah Nabawiyah provides data that has not been included in the collection of prophetic hadits (al-Ziyadah), fulfills the incomplete material presented in the collection of prophetic hadits (at-Takmil) and explores the material systematically.